Body Fat of Basketball Players: A Systematic Review and Meta-Analysis - Pierpaolo Sansone; Bojan Makivić; Robert Csapo; Patria Hume; Alejandro Martínez‐Rodríguez; Pascal Bauer (2022)
This study aimed to provide reference values for body fat (BF) of basketball players considering sex, measurement method, and competitive level.A systematic literature research was conducted using five electronic databases (PubMed, Web of Science, SPORTDiscus, CINAHL, Scopus). BF values were extracted, with analyses conducted using random-effects models and data reported as percentages with 95% confidence intervals (CI).After screening, 80 articles representing 4335 basketball players were selected. Pooled mean BF was 13.1% (95% CI 12.4-13.8%) for male players and 20.7% (95% CI 19.9-21.5%) for female players. Pooled mean BF was 21.4% (95% CI 18.4-24.3%) measured by dual-energy X-ray absorptiometry (DXA), 15.2% (95% CI 12.8-17.6%) via bioelectrical impedance analysis (BIA), 12.4% (95% CI 10.6-14.2%) via skinfolds and 20.0% (95% CI 13.4-26.6%) via air displacement plethysmography. Pooled mean BF across competitive levels were 13.5% (95% CI 11.6-15.3%) for international, 15.7% (95% CI 14.2-17.2%) for national and 15.1% (95% CI 13.5-16.7%) for regional-level players. As the meta-regression revealed significant effects of sex, measurement method and competitive level on BF, the meta-analysis was adjusted for these moderators. The final model revealed significant differences in BF between male and female players (p < 0.001). BF measured by DXA was significantly higher than that measured by BIA or skinfolds (p < 0.001). International-level players had significantly lower BF than national and regional-level players (p < 0.05).Despite the limitations of published data, this meta-analysis provides reference values for BF of basketball players. Sex, measurement method and competitive level influence BF values, and therefore must be taken into account when interpreting results.